NALISIS PENGARUH CURRENT RATIO, FIRM SIZE, DAN ASSETS TANGIBILITY TERHADAP RETURN ON ASSET DENGAN DEBT TO TOTAL ASSET SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2008-2011) - NURSATYANI, ANISA; WAHYUDI, SUGENG; SYAICHU, MUHAMAD (JURNAL BISNIS STRATEGI, 2014)
AbstractThis study to examine the effect  of Current Ratio (CR), firm size, and assets tangibility  to Return on Assets  (ROA) with Debt to Total Assets  (DTA) as an intervening  variable. Object studies at mining companies listed on Indonesia Stock Exchange during 2008-2011. Sampling technique using purposive sampling method based on particular criteria which was appropriate with research purposes.  This study use 15 mining companies. Methods of data analysis using  multiple  linear regression  analysis, path analysis, and Sobel test.The results show  Debt to Total Asset (DTA), Current Ratio (CR), and assets  tangibility  have negative effect on Return on Assets  (ROA), but firm size has not effect on Return on Assets  (ROA). Current Ratio (CR) has negative effect  on Debt to Total Assets  (DTA), but firm size and asset tangibility  have not effect on Debt to Total Assets  (DTA). Debt to Total Assets  (DTA) is able to mediate  relationship  between  Current Ratio (CR) to Return on Assets  (ROA), but is not able to mediate relationship  between firm size and assets tangibility to Return on Asset (ROA).